Meals, Education, and Gardens for In-School Adolescents (MEGA): study protocol for a cluster randomised trial of an integrated adolescent nutrition intervention in Dodoma, Tanzania - Wafaie W Fawzi; Dongqing Wang; Abbas Ismail; Leonard Kamanga Katalambula; Andrea R Modest; Tara Young; Mary Mwanyika-Sando; Amani Tinkasimile; Dominic Mosha; Augustine Malero; Said Vuai (BMJ Open)
Introduction Secondary schools have the transformative potential to advance adolescent nutrition and provide a unique entry point for nutrition interventions to reach adolescents and their families and communities. Integrated school nutrition interventions offer promising pathways towards improving adolescent nutrition status, food security and building sustainable skill sets.Methods and analysis The Meals, Education, and Gardens for In-School Adolescents (MEGA) project aims to implement and evaluate an integrated, school-based nutrition intervention package among secondary schools in the Chamwino District of Dodoma, Tanzania. MEGA is a cluster-randomised controlled trial, including six public secondary schools assigned to three different arms. Two schools will receive the full intervention package, including school meals, school gardens, nutrition education and community workshops. Two schools will receive the partial intervention package, including the school garden, nutrition education and community workshops. Two schools will serve as the controls and will not receive any intervention. The intervention will be implemented for one academic year. Baseline and end-line quantitative data collection will include 750 adolescents and 750 parents. The domains of outcomes for adolescents will include haemoglobin concentrations, anthropometry, educational outcomes and knowledge, attitudes and practices regarding nutrition, agriculture and health. The domains of outcomes for parents will include knowledge, attitudes and practices of nutrition, agriculture and health. End-line focus group discussions will be conducted among selected adolescents, parents and teachers to assess the facilitators and barriers associated with the intervention.Ethics and dissemination This study was approved by the Institutional Review Board at Harvard T.H. Chan School of Public Health (approval number: IRB20-1623), the Institutional Research Review Committee at the University of Dodoma (approval number: MA.84/261/02) and the Tanzania National Institute for Medical Research (approval number: NIMR/HO/R.8a/Vol. IX/3801). A manuscript with the research findings will be developed for publication. Local dissemination meetings will be held with key stakeholders.Trial registration number NCT04788303.; ClinicalTrials.gov Identifier.